Significant Contribution of Emotional Intelligence to The Learning Achievement of Elementary School Students - Cania, Sri; Hartini, Budi (Educational Insights, 2025)
This study aims to examine the influence of emotional intelligence on the learning outcomes of elementary school students. The research is motivated by the assumption that low academic achievement is not solely influenced by cognitive abilities but is also related to students’ emotional competencies. A quantitative approach with an associative research design was employed. The sample consisted of 240 elementary school students selected through random sampling techniques. Data were collected using closed-ended questionnaires and analyzed using simple linear regression with the assistance of SPSS software. Emotional intelligence has a positive and significant effect on learning outcomes, as evidenced by a regression coefficient of 0.627 with a significance level of < 0.001. The coefficient of determination (R²) of 0.321 shows that emotional intelligence accounts for 32.1% of the variance in students’ learning outcomes, while the remaining variance is explained by other factors beyond the scope of this study. This study strengthens the perspective that emotional intelligence is a fundamental affective construct that directly contributes to academic achievement at the elementary education level. Educators and policymakers to integrate emotional intelligence development into elementary school learning processes as part of a holistic educational approach aimed at improving students’ academic performance and emotional well-being.